Study on antiexplosion performance of reinforced concrete slabs strengthened with POZD coated steel plate under contact explosion. (October 2022) - Wang, Wei; Wei, Guangshuai; Yang, Jianchao; Liu, Fei; Gao, Weiliang
Highlights: Contact explosion experiments of reinforced concrete slabs strengthened with different thicknesses of POZD coated steel plates were carried out. The damage grade of the specimen was divided. The propagation of the explosion stress wave in the specimen was analyzed and summarized. The empirical formula of the damage of POZD coating thickness on the specimen structure under different TNT charges was given. Abstract: In recent years, new materials and protection technologies have rapidly developed with the rising worldwide terrorism. This article studied the antiexplosion performance of reinforced concrete (RC) slabs strengthened with polyisocyanate oxazolidine (POZD) coated steel plate through contact blast tests and numerical simulations. The damage mode and damage mechanism of RC slab reinforced by POZD coated steel plate were analyzed by numerical simulation. The results showed that the antiexplosion performance of steel plate-RC slab was enhanced with the increase of the coating thickness. Based on the above analysis, the empirical expressions of normalized crater diameter, back damage area diameter and POZD bulging diameter were obtained.